Pengembangan Kemampuan Berpikir Kritis Peserta Didik SMA dengan Lembar Kerja Proses pada Mata Pelajaran Fisika - Tantri Mayasari; Jeffry Handhika; Zulfawati Zulfawati (Kappa Journal, 2021)
Student worksheets (LKPD) is the most significant aspect on the learning activities because it consists of the studentâ€™s learning process of gaining  knowledge, primarily growing the critical thinking ability. The aim of the study is giving information about the development of critical thinking with LKPD process in physics subject. The method is Research and Development (RnD)-ADDIE which is limited on the development stage. Based on the evaluation result through validity which involve expert validity from the lecturer and the teacher, Content Validity Index (CVI) is 0,95 that means very suitable. The CVI result indicates that the LKPD process could be used to grow the physics critical thinking. The LKPD process has not arrived at implementation yet, hopefully the reseacher on the same field could apply till the implementation stage so that we could say LKPD process could grow the physics critical thinking.